Advanced Atrio-Ventricular Blocks in a Foal Undergoing Surgical Bladder Repair: First Step to Cardiac Arrest? - Marolf, Vincent; Mirra, Alessandro; Fouché, Nathalie; Navas de Solis, Cristobal (Frontiers in Veterinary Science, 2018)
A 3-day-old Swiss Warmblood colt was diagnosed with uroabdomen after urinary bladder rupture. The foal had classical electrolyte abnormalities (hyponatremia, hypochloremia and hyperkalemia) on presentation. The foal was supported prior to surgery with intravenous fluids and the electrolyte abnormalities were treated with physiologic saline, glucose and insulin. Urine could not be drained from the abdomen prior to surgery because the omentum was continuously occluding the drainage cannula and due to progressive abdominal distension, it was decided to pursue surgery without further correction of electrolyte abnormalities. After induction of anaesthesia, signs of hypoxemia were present. Controlled mandatory ventilation using a pressure-controlled ventilation mode with positive end-expiratory pressure was initiated. Urine was drained from the abdomen by free flow. Atrio-ventricular (AV) blocks unresponsive to intravenous antimuscarinic drugs developed. After low dose of epinephrine and cardiac massage, sinus rhythm was restored. Surgery was completed successfully and the foal recovered from anaesthesia. The postoperative period was uneventful and the foal was discharged from the hospital three days later. Based on a clinical case, the purpose of the manuscript is to provide the clinician with potential causes, prevention and treatment of this already known but rarely observed dysrhythmia which could lead to fatal consequences. Definitions of cardiac arrest and asystole are reappraised. We discuss the fact that advanced AV-blocks should be treated as a cardiovascular emergency with advanced life support. The early recognition of advanced AV blocks is the first step to reduce perioperative mortality and morbidity of foal suffering from uroabdomen.